Response Spectra Study of High Rise Structure with RC Shear Wall by Considering Lateral Loads and Storey Stiffness (Global Journals of Research in Engineering, 2024)
The present study aims at evaluation of the behavior of a high rise structure with dual system for estimation of structural response lateral loads and storey stiffness has been studied To meet this objective G 29 storey building with C shape Box shape E shape I shape and plus shape of RC shear wall at the center in concrete frame structure with fixed support conditions under different types of soil for high earthquake zone are analyzed by dynamic analysis in ETABS software It was found that the building with box shape shear walls provided at the center core showed very significant performance in terms of lateral loads and storey stiffness It was found that the behavior of new shape plus shape of shear wall is similar to I and box shape For severe lateral loads caused by wind load and or earthquake load the RC shear wall is obvious
Keywords: dynamic analysis; structural response; soil conditions; high earthquake zone; ETABS software